2021
DOI: 10.3390/agronomy11061161
|View full text |Cite
|
Sign up to set email alerts
|

Crop Response to Leaf and Seed Applications of the Biostimulant ComCat® under Stress Conditions

Abstract: Although clear evidence for benefits in crop production is partly missing, several natural compounds and microorganisms have been introduced to the market as biostimulants. They are supposed to enhance nutrient efficiency and availability in the rhizosphere, reduce abiotic stress, and improve crop quality parameters. Biostimulants often derive from natural compounds, such as microorganisms, algae, and plant extracts. In this study, the commercial plant extract-based biostimulant ComCat® was tested in two field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Interestingly enough, the activity of the antioxidant enzymes on wheat leaves, plant height, and fresh and dry weight were increased at the application with the biostimulant-soaked seeds compared to untreated seeds in which bromoxynil was used. However, in a pot experiment, a botanical extract biostimulant was evaluated as seed treatment and postemergence leaf application in wither barley, under different concentrations to overcome the herbicidal stress of cinmethylin (inhibitor of fatty acid thioesterase) [52]. Their results showed that this specific plant-based biostimulant was able to prevent excess herbicidal stress to barley's dry biomass 21 days after the seed treatment, with the application rates being insignificant.…”
Section: Effect Of Biostimulants On Mitigating Stress From Herbicidal...mentioning
confidence: 99%
“…Interestingly enough, the activity of the antioxidant enzymes on wheat leaves, plant height, and fresh and dry weight were increased at the application with the biostimulant-soaked seeds compared to untreated seeds in which bromoxynil was used. However, in a pot experiment, a botanical extract biostimulant was evaluated as seed treatment and postemergence leaf application in wither barley, under different concentrations to overcome the herbicidal stress of cinmethylin (inhibitor of fatty acid thioesterase) [52]. Their results showed that this specific plant-based biostimulant was able to prevent excess herbicidal stress to barley's dry biomass 21 days after the seed treatment, with the application rates being insignificant.…”
Section: Effect Of Biostimulants On Mitigating Stress From Herbicidal...mentioning
confidence: 99%